Integrated multi-omics reveals contrasting epigenetic patterns in leaf and root morphogenesis in Aegilops speltoides - Lingfeng Miao; Zhe Chen; Lifeng Gao; Jizeng Jia; Weilong Guo; Guangyao Zhao (Crop Journal)
Aegilops speltoides, the closest ancestor of the wheat B subgenome, has been well studied genomically. However, the epigenetic landscape of Ae. speltoides and the effects of epigenetics on its growth and development remain poorly understood. Here, we present a comprehensive multi-omics atlas of leaves and roots in Ae. speltoides, encompassing transcriptome, DNA methylation, histone modifications, and small RNA profiling. Divergent DNA methylation levels were detected between leaves and roots, and were associated with differences in accumulated 24-nt siRNAs. DNA methylation changes in promoters and gene bodies showed strong connections with altered expression between leaves and roots. Transcriptional regulatory networks (TRN) reconstructed between leaves and roots were driven by tissue-specific TF families. DNA methylation and histone modification act together as switches that shape root and leaf morphogenesis by modulating the binding of tissue-specific TFs to their target genes. The TRNs in leaves and roots reshaped during wheat polyploidization were associated with alterations in epigenetic modifications. Collectively, these results not only shed light on the critical contribution of epigenetic regulation in the morphogenesis of leaves and roots in Ae. speltoides but also provide new insights for future investigations into the complex interplay of genetic and epigenetic factors in the developmental biology of common wheat.